Comparative efficacy of aromatase inhibitors and gonadotropin-releasing hormone analogue in increasing final height of idiopathic short stature boys: a network meta-analysis - Wang, Siqi; Wu, Zhixin; Chen, Yang; Luo, Kuanhong; Cui, Zhenhai; Zhang, Jiaoyue; Zheng, Juan; Xiao, Kangli; Li, Huiqing (Frontiers in Endocrinology, 2023)
Objective To investigate the efficacy of monotherapy with AIs or GnRHa in improving the height of boys with idiopathic short stature (ISS). Method We performed a systematic search in Pubmed, The Cochrane Library, Chinese National Knowledge Infrastructure databases, and Wanfang Database for eligible studies. The network meta-analysis was conducted using STATA software. Results We identified a total of four studies that included 136 individuals. We used FAH/PAH as the main outcome of final height. The results revealed a statistically higher final height after treatment with AI or GnRHa in idiopathic short stature children(MD= 4.63, 95% CI[3.29,5.96]). In network meta-analysis, the direct and indirect comparison between AI and GnRHa was presented in the forest plot. Compared with control group, both AI and GnRHa were effective in increasing the final height, with the mean effect of 4.91(95%CI:1.10,8.17) and 5.55(95%CI:1.12,9.98) respectively. However, there was no statistical difference between the GnRHa and AI treatment, of which the mean effect was 0.65(95%CI: -4.30,5.60). Conclusion Both AIs and GnRHa monotherapy were effective in augmenting the final height of boys with idiopathic short stature when compared to placebo groups. However, there was no statistical difference between the GnRHa and AI treatments.